Evaluation of Dorper Sheep under Village and On Station Management Systems in Ethiopia - Abebe, Ayele (Amhara Regional Agricultural Research Institute, Debre Birhan Agricultural Research Center, 2024)
The study evaluated the performance of Dorper sheep and their crossbreds under both farmermanaged and semi-intensive systems across diverse regions of Ethiopia. On-farm flock monitoring of farmers’ flock and extensive assessments of productive and reproductive traits were conducted on flocks managed semi-intensively at research centers and universities. Additionally, a survey of 248 households assessed the performance of distributed Dorper sires, Dorper crossbred lambs, ewes and farmers' perceptions of the breed’s productive and adaptive traits. The data was analyzed using SAS and SPSS statistical software. The study found that sheep were the dominant livestock, accounting for 59% of holdings, with breeding ewes having the highest proportion (46%). Farmers kept sheep primarily for income, meat consumption, and savings. Farmers perceived Dorper crossbreds as superior to locals in conformation, growth, meat yield/quality (red meat), good mothering ability, and market readiness, but noted higher feed requirements. Both local and Dorper ewes lambed yearround, with peaks in Sep-Oct-Dec (35% of births), and more births (39%) in the dry season vs. 33% in the rainy season. Under semi-intensive system, conception and lambing rates were higher when using Dorper crossbred rams (90.5 and 98.5%) and local ewes (90.8 and 98.2%). Under both farmers’ and semi-intensive management, local and Dorper crossbred ewes had similar litter sizes at birth (LSB) and weaning (LSW), though affected by environment. In semi-intensive systems, local and crossbred ewes had better litter sizes than Dorper purebreds. However, Dorper crossbred and Dorper purebred ewes had higher litter weights at birth (LWB), and weaning (LWW). Ewes sired by local sires had the lowest values for LWB and LWW. Under farmers’ management, local ewes had lower age at first lambing (AFL) (14.7 vs 16.2 months) than Dorper crossbreds, but no differences in lambing interval (LI) (9.0 vs 9.6 months) or annual reproductive rate (ARR) (1.55 vs 1.42). Under semi-intensive management, AFL, LI, and ARR were affected by both genotype and environment. Ewes sired by pure bred Dorper and Dorper crossbred sires produced higher annual lamb weight per ewe (27.6 kg and 26.6 kg) in 90 days than local sires (23.4 kg) (p < 0.0001). Dorper crossbred ewes had the highest annual lamb weight (26.8 kg) compared to local (25.9 kg) and purebred Dorper (25.0 kg) ewes (p = 0.0013). No difference in annual lamb weight between local and Dorper crossbred ewes under farmers’ management, indicating effects of management. Under farmers’ management, Dorper crossbred lambs showed 39%, 31%, 34%, and 27% higher birth, 3-month, 6- month, and yearling weights, respectively, compared to local lambs. Dorper crossbreds also had 32% and 23% higher pre- and post-weaning gains. Under semi-intensive management, lamb-traits were influenced by both genetic and environmental factors, with lambs in low-mid to highland areas having higher values than those in cool-sub alpine areas. Lambs with 75% Dorper genes showed higher post-weaning trait-values. Under semi-intensive management, using 50% Dorper-F1 and 75% Dorper inheritance improved lamb birth weights by 41-64%, weaning weights by 38-52%, and preweaning growth rates by 39-50%, six-month and yearling weights were improved by 36-56% and 55- 64%, respectively. While lamb genotype did not influence survival under farmers' management, it affected survival at 3 and 6 months under semi-intensive systems due to genetic and environmental factors. In semi-intensive systems, lamb-traits were influenced by both genetics and environment, ` xx with higher Dorper inheritance (75%) improving post-weaning performance. Using 50-75% Dorper crossbreds significantly boosted lamb birth, weaning, and yearling weights compared to local sheep. Dorper purebred sheep (under a semi-intensive system) and their crossbreds under both systems demonstrated adaptability and productivity across low and high agro-ecologies. The study highlighted farmers' acceptance of Dorper sheep, but noted constraints around access to Dorper rams and improving production environments through feed development and healthcare. It emphasized the need for stakeholder coordination to ensure the success and sustainability of Dorper crossbreeding programs in Ethiopia. Indicators of Dorper crossbreed acceptance included ram distribution, rams’ adaptation, lamb Dorper inheritance, and farmer interest. However, aspects of the breeding scheme, like upgrading units and farmer linkages, were still in early stages. Incorporating up to 25% Dorper genetics into indigenous sheep for traditional, farmer-managed systems (following the CBBP practice), use 50-75% Dorper genetics for semi-intensive production to maximize productivity, promote private commercial farmers and transform breeding centers, develop an Ethiopian synthetic Dorper crossbred population, and establishment of a consolidated national Dorper coordination body are recommended.